2019
DOI: 10.3390/foods8080341
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Differentiation of Spanish Vinegars from Jerez and Condado de Huelva Protected Designations of Origin

Abstract: Thirty one Jerez vinegar samples and 33 Huelva vinegar samples were analyzed for polyphenolic and volatile compound content in order to characterize them and attempt to differentiate them. Sixteen polyphenolic compounds were quantified by means of ultraperformance liquid chromatography method with diode array detection (UPLC–DAD), and 37 volatile compounds were studied by means of stir bar sorptive extraction–gas chromatography–mass spectrometry (SBSE–GC–MS). Spectrophotometric CIELab parameters were also meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…This is in good agreement with previous studies describing the suitability of SNV for the extraction of spectral information related to antioxidants and antioxidant activity by NIR [28], and for the discrimination of Australian Shiraz wines by MIR [29]. In a previous study, vinegar samples from "Jerez" and "Condado de Huelva" PDOs were subjected to complete chemical characterization of polyphenols and volatile compounds [13]. Using these chemical descriptors, LDA analysis enabled the differentiation of the samples according to the geographical origin, although yielding lower classification performance to that provided by UV-Vis spectral data (92.86% and 94.12% of the samples were successfully classified when modeling polyphenolic and volatile data, respectively).…”
Section: Differentiation Of Vinegars According To Their Protected Designation Of Originsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in good agreement with previous studies describing the suitability of SNV for the extraction of spectral information related to antioxidants and antioxidant activity by NIR [28], and for the discrimination of Australian Shiraz wines by MIR [29]. In a previous study, vinegar samples from "Jerez" and "Condado de Huelva" PDOs were subjected to complete chemical characterization of polyphenols and volatile compounds [13]. Using these chemical descriptors, LDA analysis enabled the differentiation of the samples according to the geographical origin, although yielding lower classification performance to that provided by UV-Vis spectral data (92.86% and 94.12% of the samples were successfully classified when modeling polyphenolic and volatile data, respectively).…”
Section: Differentiation Of Vinegars According To Their Protected Designation Of Originsupporting
confidence: 90%
“…Altogether, it becomes evident that the food industry requires robust analytical methodologies to characterize the quality and verify the geographical origin of vinegars. In this context, several studies have previously reported the possibility of discriminating vinegars by using classical targeted approaches based on atomic emission spectroscopy, gas chromatography-mass spectrometry and high-performance liquid chromatography for the determination of mineral elements [10], volatile compounds [11][12][13], as well as polyphenols, organic acids and amino acids [13,14], respectively. Although these methods generally provide high accurateness and sensitivity, they are also time consuming and require considerable amounts of toxic and expensive chemical solvents and reagents.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing Sherry vinegars to vinegars from other Protected Designation of Origins (PDO), Ríos-Reina et al [ 72 ] carried out a study for the discrimination of vinegars from the three vinegar Protected Designation of Origin (PDO)s in Spain (‘Sherry Vinegar’, ‘Vinegar of Condado de Huelva’, and ‘Vinegar of Montilla-Moriles’). Other authors evidenced that the volatile content in vinegar is influenced not only by the production process, which is similar for Sherry vinegars and vinegars from Huelva, but also by the raw material, in this case, the grape variety used, Palomino for Sherry PDO and Zalema for Huelva PDO, as well as by geographical factors associated to each PDO [ 73 ]. Other authors [ 90 ], compared Sherry vinegars to vinegars from Huelva PDO and from Montilla-Moriles PDO, and some of their volatile compounds, namely 1-heptanol, methyl nonanoate, 2-methylbutanoic acid, 2,2,6-trimethyl-cyclohexanone, trans-2-decenal, eucalyptol, and α-terpineol allowed the differentiation of Huelva PDO vinegars from those produced under the Sherry PDO and Montilla-Moriles PDO, while diacetyl, acetoin, ethyl 3-ethoxypropanoate, 2- and 3-heptanone, 2-methyl-1-hexadecanol, 1-octen-3-ol, p-cresol, and camphene allowed to differentiate the vinegars from the Montilla-Moriles PDO.…”
Section: Study Of the Aroma Of Sherry Vinegarmentioning
confidence: 96%
“…When comparing Sherry vinegars to vinegars from other Protected Designation of Origins (PDO), Ríos-Reina et al [72] carried out a study for the discrimination of vinegars from the three vinegar Protected Designation of Origin (PDO)s in Spain ('Sherry Vinegar', 'Vinegar of Condado de Huelva', and 'Vinegar of Montilla-Moriles'). Other authors evidenced that the volatile content in vinegar is influenced not only by the production process, which is similar for Sherry vinegars and vinegars from Huelva, but also by the raw material, in this case, the grape variety used, Palomino for Sherry PDO and Zalema for Huelva PDO, as well as by geographical factors associated to each PDO [73]. Other authors [90], compared Sherry vinegars to vinegars from Huelva PDO and from Montilla-Moriles PDO, and some of their volatile compounds, namely 1-heptanol, methyl nonanoate, 2-methylbutanoic acid, 2,2,6-trimethyl-cyclohexanone, trans-2-decenal, eucalyptol, When comparing Sherry vinegars to vinegars from other Protected Designation of Origins (PDO), Ríos-Reina et al [72] carried out a study for the discrimination of vinegars from the three vinegar Protected Designation of Origin (PDO)s in Spain ('Sherry Vinegar', 'Vinegar of Condado de Huelva', and 'Vinegar of Montilla-Moriles').…”
Section: Study Of the Aroma Of Sherry Vinegarmentioning
confidence: 81%